Long-term effects on the incidence of second primary cancers in a randomized trial of two and five years of adjuvant tamoxifen. (3rd April 2017) - Rosell, Johan; Nordenskjöld, Bo; Bengtsson, Nils-Olof; Fornander, Tommy; Hatschek, Thomas; Lindman, Henrik; Malmström, Per-Olof; Wallgren, Arne; Stål, Olle; Carstensen, John
Abstract: Background: Tamoxifen is a well established treatment for breast cancer, but its long-term effects on the incidence of secondary cancers are not fully evaluated. Material and methods: We have studied 4128 postmenopausal patients with early stage breast cancer who were alive and free of breast cancer recurrence after two years of tamoxifen, and who were randomized to receive totally two or five years of therapy. Results: Compared to patients randomized to two years of tamoxifen the incidence of contralateral breast cancer [hazard ratio (HR) 0.73; 95% CI 0.56–0.96] and of lung cancer (HR 0.45; 95% CI 0.27–0.77), especially squamous cell and small cell lung cancer, were reduced in the five-year group, and similar results were seen when restricting the analysis to the 10-year period after treatment stopped. An increased incidence of endometrial cancer was observed in the five-year group, but the excess risk decreased over time. Conclusion: Further studies of the effects of tamoxifen on the risk of different histological types of lung cancer are needed.